ANALISIS PEMASARAN KENTANG MANIS (Ipomeae batatas L) PADA KELOMPOK TANI MAKMUR DI DESA PUNTUKREJO KECAMATAN NGARGOYOSO KABUPATEN KARANGANYAR - Dewi Wulan Sari; Suswadi Suswadi; Handayani Handayani (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2017)
Sweet potato (Ipomeae batatas L) is one of the potential crops of palawija to be developed as a substitute for rice. Karanganyar Regency, especially Ngargoyoso District is one of the areas that cultivate sweet potato crops. Because there is no clear marketing channel, therefore it is necessary to study the marketing channel of sweet potato in Puntukrejo Village, Ngargoyoso District, Karanganyar Regency.The basic method used is descriptive analytical. The method of determining the location of the research intentionally is in the Puntukrejo Village, Ngargoyoso District, Karanganyar Regency. Methods of responding farmers is by convinience sampling and in 30 farmers of respondents. Method of taking respondents of marketing actors by using snowball sampling. The data used are primary data and secondary data.Analytical methods used are analysis of marketing functions, marketing costs, marketing benefits, and margin and marketing efficiency. The results showed the average total production cost of sweet potato is Rp. 5.206.759.04. The average revenue received by farmers is Rp. 10,274,000.00. Revenue earned by farmers is Rp. 5,239,050.00. There are three marketing channels of sweet potato in Puntukrejo Village, Ngargoyoso Sub-district, Karanganyar Regency, Marketing Channel patterns I : farmers → wholesalers → small traders → consumers, Marketing Channel II : farmers → merchant collectors → wholesalers → small traders → consumers, Marketing Channel III : farmer → wholesaler → factory / consumer. The average total marketing cost on marketing channel I is Rp. 1,022 / kg and the total profit average of Rp. 699.84 / kg. In marketing channel II, the average total marketing cost is Rp. 1,127.16 / kg and the average total profit is Rp. 742.07 / kg. The average total marketing cost on marketing channel III is Rp. 747,23 / kg and the average profit on marketing channel III Rp. 252.77 / kg. Marketing margin on marketing channel I is Rp. 1,722,73 / kg, with farmer's share of 53.72%. On marketing channel II the marketing margin is Rp. 1,869.23 / kg, and farmer's share of 52.72%. Marketing margin on marketing channel III is Rp. 1,000.00 / kg and farmer's share of 67.39%. Based on these results, the most efficient marketing channel is marketing channel III, because it has the lowest marketing margin value so that the value of farmer's share is highest.